OPTIMASI ALOKASI AIR IRIGASI MENGGUNAKAN PROGRAM LINIER (STUDI KASUS BENDUNGAN BATU BULAN KEC. MOYO HULU) - Hermanto, Koko; Utami, Silvia Firda; Suarantalla, Ryan (PATTIMURA UNIVERSITY, 2020)
The area of the Batu Bulan dam is less than 183 hectares with capacity of 15 liters per second, the largest dam on Sumbawa island, located in Batu Bulan village, Moyo Hulu sub-district, Sumbawa regency, West Nusa Tenggara. Batu Bulan Dam is planned to be able to meet the irrigation needs, raw water, and has a potential for hydroelectric power plants. Considering the latter plans and the limited water supply from the dam, it is necessary to have a study for the optimization of the Dam's water allocation. By this study, the water allocation can be optimized and the planting patterns are managed. The goal of this research is the optimization of Batu Bulan Dam waters allocation for irrigation utilization, which is expected to improve dam operation patterns, to obtain the best cropping patterns and to obtain optimum benefits of rice and corn plants planted in the irrigation area. One method that can be used to solve the water allocation problem is linear programming with the objective is maximizing total profits and the constraints is water availability and land area